PENGARUH DYNAMIC WORKING ARRANGEMENT DAN LITERASI DIGITAL TERHADAP PRODUKTIVITAS PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS PEMBERDAYAAN MASYARAKAT DAN DESA PROVINSI JAWA BARAT - Irvan Taufiq; Mochamad Vrans Romi (ITB AAS Indonesia Surakarta, 2025)
Changes in work requirements in the digital era and budget efficiency policies require civil servants to improve flexibility and efficiency in their work. In line with this, the West Java Provincial Government has implemented dynamic working arrangements (DWA) that must be supported by good digital literacy skills. However, the implementation of DWA allows employees to engage in unproductive activities, resulting in suboptimal employee productivity. This study aims to analyze the level of employee productivity influenced by dynamic working arrangements, digital literacy, and job satisfaction as intervening variables at the West Java Provincial Department of Community Empowerment and Village Development. The study population consists of 87 civil servants. The sampling technique used is purposive sampling. Data collection techniques used questionnaires. Data analysis techniques included validity and reliability tests, classical assumption tests, path analysis, hypothesis testing, Sobel tests, and correlation analysis. Data processing tools used SPSS 24. The results showed that DWA positively influences job satisfaction. Digital literacy does not positively influence job satisfaction. Job satisfaction has a positive effect on productivity. DWA does not have a direct effect on productivity. Digital literacy has a direct effect on productivity. Job satisfaction can mediate the effect of DWA on productivity. Job satisfaction cannot mediate the effect of digital literacy on productivity.